Altered dynamic functional connectivity of motor cerebellum with sensorimotor network and default mode network in juvenile myoclonic epilepsy - Yang, Menghan; Zhang, Yingying; Zhang, Tianyu; Zhou, Huanyu; Ren, Jiechuan; Zhou, Dong; Yang, Tianhua (Frontiers in Neurology, 2024)
Abstract Objective: To investigate whether changes occur in the dynamic functional connectivity (dFC) of motor cerebellum with cerebral cortex in juvenile myoclonic epilepsy (JME). Methods: We adopted resting-state electroencephalography - functional magnetic resonance imaging (EEG-fMRI) and a sliding-window approach to explore the dFC of motor cerebellum with cortex in thirty-six JME patients compared with thirty and age-matched health controls (HCs). The motor cerebellum was divided into five lobules (I–V, VI, VIIb, VIIIa, and VIIIb). Additionally, correlation analyses were conducted between the variability of dFC and clinical variables in the Juvenile Myoclonic Epilepsy (JME) group, such as disease duration, age at disease onset, and frequency score of myoclonic seizures. Results: Compared to HCs, the JME group presented increased dFC between the motor cerebellum with SMN and DMN. Specifically, connectivity between lobule Ⅶb and left precentral gyrus and right inferior parietal lobule (IPL); between lobule Ⅷa and right inferior frontal gyrus (IFG) and left IPL; and between lobule Ⅷb and left middle frontal gyrus (MFG), bilateral superior parietal gyrus (SPG), and left precuneus. In addition, within the JME group, the strength of dFC between lobule Ⅷb and left precuneus was negatively (r=-0.424, p=0.025, Bonferroni correction) related with the frequency score of myoclonic seizures. Conclusion: In patients with JME, there is a functional dysregulation between the motor cerebellum with DMN and SMN, and the variability of dynamic functional connectivity may be closely associated with the occurrence of motor symptoms in JME.